Formulation of Dairy-Free Imitation Cream Cheese with Fat Substitute Cocoa Butter Substitute (CBS) - Fikri, Ilham; Priyono, Suko; Saputri, Nur Endah; Maulana, Hamzah Akram (FoodTech: Jurnal Teknologi Pangan, 2025)
Cream cheese is often used as a salad dressing, spread on bread, sauce, and beverage topping. This study aims to find out the appropriate ratio of soy milk curd with CBS for the best physicochemical and sensory dairy-free imitation cream cheese (DFICC). The design of this study used a Group Randomized Design (GRD) with 1 factor, i.e., soy milk curd: CBS ratio mass, consisting of 5 treatment levels. Each treatment was subjected to group replication for a total of 5 replicates, thus obtaining 25 experimental units. The data of observation results obtained will be statistically analyzed by using Analysis of Variance (ANOVA). If the treatment has a real influence, then followed by the Honest Real Difference (HD) test at the 5% level. Sensory analysis will be performed using a scoring descriptive test (Scoring Test), and the data obtained will be analyzed using the Kruskal-Wallis method. Determination of the best treatment using effectiveness index testing. The best chemical and sensory characteristics of dairy free imitation cream cheese were obtained in the formulation of 75g of soy milk curd: 25g of CBS which has a treatment value (NP) of 0.69 with water content of 46.23%, protein content of 4.73%, fat content of 36.46%, pH of 4.17, sensory value, color, sensory value, color 3.00, aroma sensory value 2.83, taste sensory value 2.83, smear power sensory value 3.17 and overall sensory value 3.10.